Unraveling Incongruence: The EU Proposal in the Belgrade-Pristina Dialogue - A. Semenov; I. Baščarević (Vestnik MGIMO-Universiteta)
This paper explores the complexities surrounding the acceptance of the European Union (EU) Proposal in the ongoing Belgrade-Pristina dialogue. The incongruence between Belgrade and Brussels is shaped by several interrelated factors. Central to this discord is the premature transfer of authority from the United Nations Mission in Kosovo (UNMIK) to the EU. This transition was prompted by UNMIK's failure to safeguard Kosovo's non-Albanian population and the breakdown of status negotiations, culminating in Kosovo’s unilateral declaration of independence. Although the EU has facilitated technical agreements that have supported the region's trajectory toward European integration, it has also encountered significant challenges. Notably, the withdrawal of Kosovo Serbs from political, judicial, and law enforcement institutions, compounded by the destabilizing effects of the Ukraine conflict, has intensified the crisis. These dynamics have accelerated a reliance on informal agreements, which circumvent domestic legislative processes and are characterized by a lack of transparency. The EU Proposal seeks to expedite the normalization process but contains a contentious provision that implicitly demands Serbia's acceptance of Kosovo's independence—an issue perceived in Serbia as a transgression of its core national interests. While the proposal lacks formal legal bindingness, the EU wields considerable influence, applying pressure on Serbia through mechanisms such as economic sanctions. However, such measures risk exacerbating anti-EU sentiment within Serbia. The paper argues that the EU’s strategy, which emphasizes informal agreements and seeks to avoid overt confrontation, may yield eventual progress but also risks entrenching political tensions within Serbia and Kosovo. The long-term implications of this approach remain uncertain, posing potential challenges for the stability of the EU and the broader Western Balkans region.